Clustering of NLRP3 induced by membrane or protein scaffolds promotes inflammasome assembly - Elvira Boršić; Taja Železnik Ramuta; Sara Orehek; Mateja Erdani Kreft; Matthias Geyer; Roman Jerala; Iva Hafner-Bratkovič (Nature Communications)
Abstract NLRP3 is a pattern recognition receptor forming an inflammasome in response to diverse pathogen and self-derived triggers, but molecular insights on NLRP3 activation are still lacking. Here, we drive ectopic NLRP3 to different subcellular locations in NLRP3-deficient macrophages to map the spatial activation profile of NLRP3, and find that NLRP3 variants enriched at the organellar membranes respond to canonical triggers similarly to wild-type NLRP3; however, unlike wild-type, these NLRP3 variants can be activated even in the absence of the polybasic phospholipid-binding segment. Mechanistically, membrane or protein scaffolds mediate NLRP3 clustering, which leads to the unfastening of the inactive NACHT domain conformation preceding the activated NLRP3 oligomer formation. Our data thus suggest that scaffold-promoted clustering is an important step in NLRP3 activation, enabling NLRP3 to sense distinct activator-induced cellular anomalies exhibited via lipid or protein assemblies, thereby establishing NLRP3 as the master sensor of perturbations in cell homeostasis.